1996
DOI: 10.1084/jem.183.4.1777
|View full text |Cite
|
Sign up to set email alerts
|

A predictable sequential determinant spreading cascade invariably accompanies progression of experimental autoimmune encephalomyelitis: a basis for peptide-specific therapy after onset of clinical disease.

Abstract: SummaryThe development of autoimmune disease is accompanied by the acquired recognition of new self-determinants, a process commonly referred to as determinant spreading. In this study, we addressed the question of whether determinant spreading is pathogenic for progression of chronic-relapsing experimental autoimmune encephalomyelitis (EAE), a disease with many similarities to multiple sclerosis (MS). Our approach involved a systematic epitope mapping of responses to myelin proteolipid protein (PLP) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
185
2
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(194 citation statements)
references
References 54 publications
6
185
2
1
Order By: Relevance
“…Another possible explanation, particularly in the case of CNS demyelinating disease, is de novo priming of self-reactive T cells to sequestered (auto)Ag epitopes released as a result of the primary immune response. However, there is a significant difference between epitope spreading in chronic rejection (71,72) and that in demyelinating diseases (73)(74)(75)(76)(77). To date, all epitope spreading responses in chronic rejection are recognizing allogeneic HLA-DR epitopes, dominant or cryptic, but do not recognize self-determinants (71,72).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible explanation, particularly in the case of CNS demyelinating disease, is de novo priming of self-reactive T cells to sequestered (auto)Ag epitopes released as a result of the primary immune response. However, there is a significant difference between epitope spreading in chronic rejection (71,72) and that in demyelinating diseases (73)(74)(75)(76)(77). To date, all epitope spreading responses in chronic rejection are recognizing allogeneic HLA-DR epitopes, dominant or cryptic, but do not recognize self-determinants (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Intermolecular and intramolecular epitope spreading has been demonstrated in the proliferative responses of PBMC to synthetic peptides of the hypervariable region of 32 HLA-DR alleles (71,72). Epitope spreading has been originally described in autoimmune demyelinating diseases of the CNS (73)(74)(75)(76)(77), and it is defined as the generation of de novo immune responses to epitopes different from and noncross-reacting to those that initially induced the immune response. This definition (73)(74)(75)(76)(77) is extended now to the immunity against grafts (71,72) and to the immunity against tumors (78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, TSP1 was first described as an inhibitor of angiogenesis, as it blocked the formation of new blood vessels in the cornea in vivo in response to basic FGF (1,3) and blocked endothelial cell tube formation and cell migration in vitro (2). Additional studies showed that TSP1 could serve as a naturally occurring tumor suppressor by inhibiting tumor angiogenesis (3).…”
Section: Tsp1 and Tsp2mentioning
confidence: 99%
“…Early developments in the field of angiogenesis research led to the discovery of many angiogenesis-stimulating factors, including the well-known VEGF, and to the discovery of naturally occurring angiostatic agents, such as the thrombospondins (TSPs) (1-3). TSP1 was the first naturally arising angiogenesis inhibitor to be described (1)(2)(3). Shortly thereafter, a second TSP, TSP2, was also found to inhibit angiogenesis (4).…”
Section: What Cellular and Molecular Factors Propagate The Spread?mentioning
confidence: 99%